One health capacity building in sub-Saharan Africa (2016)
Africa of late has been faced with challenges that require a multidisciplinary and multisectoral approach to address them, and academic and non-academic institutions have played a key role in training and conducting research that would promote the One Health approach. Objectives: The objective of this review was to document networks and organizations conducting One Health training, research, and outreach in Africa, as one of a series of articles around the world. Methods: Data for this review were collected from organizations through key contacts of the authors and their knowledge of networks they have worked with. Web searches were conducted using One Health, training, and research as key words for work done in Africa. Results: Africa has major networks involved in One Health training, research, and outreach, with participation of both academic and non-academic institutions. This review highlights an effort in Africa to form networks to conduct multidisciplinary training and research. The main networks include Afrique One, Southern Africa Centre for Infectious Disease Surveillance (SACIDS), and One Health Central and Eastern Africa (OHCEA). Conclusions: Both academic and non-academic institutions and organizations have shown an interest to conduct multidisciplinary training and research in Africa for managing challenges that Africa is facing currently, especially the outbreak of infectious diseases.